Inter Sequence Pause Days, Egg Production, Steroid and Luteinizing Hormone in Domestic Hen (Gallous domesticus) Immunized Against cProlactin - Reddy, I.J.; David, C.G.; Raju, S.S. (International Journal of Poultry Science, 2006)
Prolactin (PRL) is a versatile hormone synthesized and secreted by the specialized cells in vertebrate anterior pituitary and is one of the important hormone involved in regulating endocrine hormones and egg production in birds. The aim of this study was to lower the cPRL concentration in White leg horn birds (WLH) by active immunization against cPRL during the productive period (from 19-72 weeks of age), for studying and comparing the effects of low prolactin levels on the circulating concentrations of luteinizing hormone (LH), progesterone, estradiol, sequence length, intersequence pause days and egg production with the control birds of the same age group. WLH birds at 13 weeks of age were divided into two experimental groups consisting of 21 birds each in control and immunized birds. At 17th week of age, 21 birds were immunized with cPRL (conjugated with keyhole limpet haemocyanin KLH-cPRL), followed by three booster doses at four weekly intervals with a total of four immunizations. Controls were given placebo in place of immunogen. Active immunization of the birds against cPRL significantly (P< 0.01) decreased the circulating PRL concentration. cPRL antibody titers were checked at monthly intervals and found from 20th week of age to age to till 72 weeks of age in immunized birds. Estradiol, progesterone and LH concentrations were increased significantly (P< 0.01) during and after the withdrawal of immunizations. Egg production was positively correlated with estradiol-17 β (r=0.42) progesterone (r=0.52) and LH (r=0.75), whereas cPRL level was negatively correlated with egg production (r=-0.14), estradiol-17 β (r= -0.25) progesterone (r=-0.32) and LH (r=-0.15). The total number of pause days during the production period decreased significantly (p< 0.01) in the immunized group resulting in a 5.40% increase in egg production. It is concluded that there is a consistent relationship between plasma prolactin in the physiological range, intersequence pauses and laying performance in domestic hen.